Behavioral Factors and Practices of Multiple Injection Immunization for Children Aged 9-12 Months in Rural Areas - Sriatmi, Ayun; Pratiwi , Setyo Endah; Agushybana , Farid (Al-Sihah : The Public Health Science Journal, 2024)
Immunization has been proven to be cost-effective and globally successful in reducing child deaths from infectious diseases. However, the many types of vaccines that must be given to each child in one visit make this practice controversial because they are considered unsafe. The study aims to analyze behavioral determinants of multiple injection immunization practices in rural areas. This is analytical research with a quantitative and cross-sectional approach. The population consists of all children aged 9-12 months in Kendal Regency with a sample of 407 children. Respondents were parents/caregivers selected from 30 PHC. Data were collected by interview using a questionnaire that had been tested for validity and reliability. Immunization practices are assessed through the Maternal and Child Health-Book. Immunization practice with multiple injections is partially related to education, knowledge, perception (susceptibility, severity, side effects, benefits), self-efficacy, and support (family, health workers, community, informational, and policy). Simultaneously, it is known that health worker support has the most dominant influence, followed by informational support, knowledge, perceived severity, and perceived susceptibility. Efforts are needed to increase health workers' competency in reducing the pain of children due to vaccination, as well as providing education to parents/caregivers effectively through clear communication, reducing misinformation and misperceptions, especially for rural communities.